TI_GERICHTE 52.2022.251 vom 15. Juli 2022 , Multa LEPICOSC - Responsabilità di una ditta iscritta all'albo per aver funto da prestanome - TI Tribunale d'appello (2022)
Multa LEPICOSC - Responsabilità di una ditta iscritta all'albo per aver funto da prestanome